Five Basic Pillars of the Islamic Religious Education Curriculum from QS. Al-Baqarah 177 Towards a Devout Character - Nur Asiah Jamil Br Tumangger; Sarwadi Sulisno (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Surah Al-Baqarah, verse 177, contains comprehensive Islamic educational values and forms the basis of the Islamic Religious Education (PAI) curriculum. This verse teaches five main aspects that must be inherent in Islamic education: faith, worship, mu’amalah (transactions), keeping promises, and patience. The faith aspect encompasses belief in Allah SWT, the Angels, the prophets, the Holy Scriptures, the Day of Judgment, and the decree of good and evil, serving as a spiritual foundation that shapes the character of faithful and pious students. The worship aspect includes prayer, fasting, zakat, almsgiving, and the Hajj pilgrimage, as ritual practices that must be mastered. Mu'amalah, or social interaction, emphasizes responsibility towards family, the environment, and the wider community, including assisting orphans, the poor, travelers, and freeing my servants. Keeping promises reflects an attitude of trustworthiness, responsibility, and trust that must be cultivated in students. Lastly, patience in facing life's trials, such as hardship, suffering, and difficulties, is a mental and spiritual strength that is very important for the formation of a mature and steadfast soul. The PAI curriculum based on this verse aims to form people who are not only academically competent but also spiritually strong and have noble character, ready to face life with faith, morals, and social concern.